Aberrant astrocytes impair vascular reactivity in Huntington disease. Issue 2 (30th June 2015) - Hsiao, Han‐Yun; Chen, Yu‐Chen; Huang, Chien‐Hsiang; Chen, Chiao‐Chi; Hsu, Yi‐Hua; Chen, Hui‐Mei; Chiu, Feng‐Lan; Kuo, Hung‐Chih; Chang, Chen; Chern, Yijuang
<x xml:space="preserve">Abstract</x> Objective Huntington disease (HD) is an inherited neurodegenerative disease caused by the mutant huntingtin gene (mHTT), which harbors expanded CAG repeats. We previously reported that the brain vessel density is higher in mice and patients with HD than in controls. The present study determines whether vascular function is altered in HD and characterizes the underlying mechanism. Methods The brain vessel density and vascular reactivity (VR) to carbogen challenge of HD mice were monitored by 3D ΔR2‐mMRA and blood oxygenation level–dependent (BOLD)/flow‐sensitive alternating inversion recovery (FAIR) magnetic resonance imaging (MRI), respectively. The amount of vascular endothelial growth factor (VEGF)‐A and the pericyte coverage were determined by immunohistochemistry and enzyme‐linked immunosorbent assay in human and mouse brain sections, primary mouse astrocytes and pericytes, and human astrocytes derived from induced pluripotent stem cells. Results Expression of mHTT in astrocytes and neurons is sufficient to increase the brain vessel density in HD mice. BOLD and FAIR MRI revealed gradually impaired VR to carbogen in HD mice. Astrocytes from HD mice and patients contained more VEGF‐A, which triggers proliferation of endothelial cells and may be responsible for the augmented neurovascular changes. Moreover, an astrocytic inflammatory response, which reduces the survival of pericytes through an IκB kinase–dependent pathway, mediates the low pericyte coverage of blood vessels in HD brains. Interpretation Our findings suggest that the inflammation‐prone HD astrocytes provide less pericyte coverage by promoting angiogenesis and reducing the number of pericytes and that these changes can explain the inferior VR in HD mice. The resultant impaired VR might hinder cerebral hemodynamics and increase brain atrophy during HD progression. Ann Neurol 2015;78:178–192